Operational disruption and the Hungarian real time gross settlement system (VIBER) - Ágnes Lublóy; Eszter Tanai (Magyar Nemzeti Bank, 2008)
Central bankers wish to ensure worldwide that large-value transfer systems, as a component of the key market infrastructure, exhibit sufficiently robust levels of operational resilience. We focus on the operational resilience of the Hungarian real time gross settlement system, known as VIBER. The goal of the research is the quantitative assessment of the ability of the system to withstand certain types of operational shocks. Systemically important participants are identified and it is argued that they overlap with endangered participants. An indicative list of participants who might be endangered by a liquidity shock is compiled by analysing proxies for liquidity risk. We shed light on the capacity of the system to function smoothly in the event of operational problems by simulating the technical default of one or two systemically important participants in VIBER. Altogether six plausible scenarios were formed, three entire-day incidents and three incidents involving less time (part-time incidents). The impact of behavioural reactions of technically non-defaulted participants and the application of existing backup procedures are also considered. The disturbance in the payment system was measured by the value of initially not submitted payments, the value of rejected payments, the total value of queued payments, the maximum queue value, the average queue length and the settlement delay. By means of gross and net liquidity deficit indicators, liquidity assistance required to settle all previously rejected transactions is calculated. By comparing the value of unsettled payments with the value of eligible collaterals in the banks' balance sheet, we can gain insight into whether the liquidity deficit can be financed through normal monetary policy operations.
Keywords: E50; G10; G21; L10; L14; 330; real-time gross settlement; large-value transfer system; operational risk; shock-absorbing capacity; Zahlungsverkehr; Betriebliche Störung; Operationelles Risiko; Simulation; Ungarn